Agricultural residues-based activated carbons impregnated with chitosan nanoparticles by hydrothermal treatment. Issue 1 (1st January 2022) - Cruz, G J F; Aguirre, D; Canepa, C; Gómez, M M; Solís, J L; Santiago, J; Solís-Castro, R L; Cruz, J F; Keiski, R L
Abstract: Much research related to the production of materials with high-quality adsorption capacity from agricultural residues has been done. However, the adsorbents themselves do not have the antibacterial capacity, an essential property in different water treatment applications. Hydrothermal treatment is an environmentally friendly approach to impregnated nanoparticles over a substrate. This paper aims to obtain and characterize activated carbon made of corn cob and red mombin seed impregnated with chitosan via the hydrothermal treatment to be tested as an antibacterial material for aqueous phase applications. The FESEM micrographics, RAMAN spectroscopy, and FTIR-ATR analyses confirmed the presence of chitosan nanoparticles (NPs) over the surface of the activated carbons. The impregnation of Chitosan NPs affected the pore size distribution in the activated carbon, but not total pore surface area or pore volume. The impregnation of chitosan increases the antibacterial capacity against Escherichia coli and Shigella flexneri .